Hubungan Pengetahuan Ibu Post Partum Tentang Perawatan Luka Perineum Dengan Proses Penyembuhan Luka di Puskesmas Bontoa Kabupaten Maros - Hariati, Andi (Jurnal Ilmiah Amanah Akademika, 2021)
Background : Perineal rupture occurs almost in all first labor and is not uncommon in subsequent labor. The perineal rupture generally occurs in the midline and may become widespread if the fetal head is born too soon, the pubic arch angle is smaller than usual, the fetal head passes through the pelvic door that is larger in size than the subregional subreglysia of bregmatika. Perineal wound is the injury to the urogenital diaphragm and the leucator ani muscle, which occurs during normal labor, or labor with the device, can occur without injury to the skin of the perineum or to the vagina, so that it is not visible from the outside. Objective : To prove the relationship of post partum mother knowledge about perineal wound care with wound healing process. Method : This research is an analytic survey with cross sectional approach, the research population is all post partum mothers in Bontoa Healt Care Maros from August to September 2021 that is as many as 32 mothers. The sampling technique in this research was done by total population technique. Results : The study found that 32 respondents of the majority of respondents' knowledge about perineal wound care were sufficient as many as 15 people (46.9%) and well knowledgeable minority as many as 8 people (25%), normal wound healing as many as 12 people (37.5% ) and a rapid minority of 9 (28.1%). Chi-Square test results (Chi-Square person) with p value 0.00 <α = 0.05 where H0 rejected and Ha accepted. Conclusion : there is a significant relationship between mother's knowledge about perineal wound care with wound healing process.